The Contribution of Micro, Small, and Medium Enterprises to Job Creation in the Limpopo Province of South Africa; Prospects and Constraints. - Mavhungu Elias Musitha; Anna Phuti Maloma (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
With the rising unemployment and poverty in South Africa, there is a need to undertake studies to provide alternative sectors that can contribute to job creation. This study aims to present scientific evidence on the contribution of micro, small, medium enterprises (MSMEs) to job creation in Limpopo and also finding out possible prospects and constraints they face. It also wanted to offer policy makers opportunities to plan for MSMEs. Literature review and key informant interviews through focus group interview were used to gather data for this study. Purposive sample was adopted for this study. A total of twelve (12) tourism enterprises participated in the study. This study argues that MSMEs have capacity to create job opportunities. The other finding is that government officials are not keen to support MSMEs operating in townships. Lack of government is serious constraint they face. It recommends that planners should formulate policies that make it compulsory for government to procure goods and services from MSMEs.